An assessment of Credit Management and Collection System of LBP-Assisted Cooperatives in Iloilo City - Hinlo, Rowena R.
The study focused mainly on the Credit Management and Collection System of cooperatives assisted by Landbank through its Passi, Sara and Iloilo branches. The participants of the study were 35 randomly selected LBP fieldmen, Cooperative Management Technicians, and Institutional Building partners from the Integrated Rural Financing, Cooperative Development Assistance Group and Landbank Countryside Development Foundation, Incorporated. These 35 participants have worked with LBP-assisted cooperatives in the Province of Iloilo. The descriptive method of investigation was employed. A checklist was devised by the researcher to gather the data. Findings revealed that an efficient and effective Coop Credit Management and Collection System is attributed to higher educational attainment of coop officials and members, attendance in pre-membership seminar and participation in meetings, hiring of a bookkeeper to maintain financial records which are subjected to a regular audit and adherence to credit and collection policies. The study also revealed that majority of coop auditors did not send confirmation letters to validate the existence of the member-borrowers and the amount borrowed against records as well as non-visitation by coop officials to member-borrowers to closely monitor the account. These are indications of a poor coop credit management and collection system. The researcher recommended that replication of this study be made on a wider scope involving other variables such as collection techniques/schemes and fund management to further improve the coop's credit management and collection system.